Intermittent fasting for obesity and related disorders: unveiling myths, facts, and presumptions - Halpern, Bruno; Mendes, Thiago Bosco [UNESP] (Sbem-soc Brasil Endocrinologia & Metabologia, 2021)
Intermittent fasting (IF) is an increasingly popular method of weight loss, as an alternative to daily caloric restriction (DCR). Several forms of IF exist, such as alternate-day fasting or time-restricted feeding regimens. Some of its proponents claim several health benefits unrelated to caloric restriction or weight loss, which rely mainly on animal models. Although several studies published in the last few years confirm that IF can be a useful and safe therapeutical option for obesity and related disorders, no superiority to conventional caloric restriction diets have emerged.There are still several questions left answered. In this Review, we discuss some of the claims, unveiling myths, facts, and presumptions about several models of IF. The focus of this article is obesity, but there is a brief discussion of the potential benefits of IF on overall human health.
Keywords: Obesity; intermittent fasting; type 2 diabetes; weight loss; diets; insulin resistance; circadian rhythm